2020
DOI: 10.2471/blt.20.251405
|View full text |Cite
|
Sign up to set email alerts
|

Development and implementation of guidelines for the management of depression: a systematic review

Abstract: Objective To evaluate the development and implementation of clinical practice guidelines for the management of depression globally. Methods We conducted a systematic review of existing guidelines for the management of depression in adults with major depressive or bipolar disorder. For each identified guideline, we assessed compliance with measures of guideline development quality (such as transparency in guideline development processes and funding, multidisciplinary aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 73 publications
0
28
0
Order By: Relevance
“…According to the available data, recommendations for the prevention, screening, and treatment of depression have been developed in many countries around the world. The recent review of guidelines for the management of depression identified all national ( n = 82) and international ( n = 13) clinical practice guidelines from around the world [ 28 ]. All these recommendations were developed in the 21 st century and are updated periodically.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the available data, recommendations for the prevention, screening, and treatment of depression have been developed in many countries around the world. The recent review of guidelines for the management of depression identified all national ( n = 82) and international ( n = 13) clinical practice guidelines from around the world [ 28 ]. All these recommendations were developed in the 21 st century and are updated periodically.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies emphasize the need to develop recommendations in individual countries, taking into account various cultural factors as well as the specificity of the healthcare system in a given country [ 70 ]. A recent review of guidelines for the management of depression summarized all worldwide clinical practice guidelines [ 28 ]. The authors of this review also stressed the importance of considering the strategies to implement recommendations in given countries.…”
Section: Discussionmentioning
confidence: 99%
“…Management protocols are now being reviewed to improve understanding and address the intense social and economic burdens that accompany depression (44), although comprehensive guidelines are lacking in many countries and only 25% of guidelines identify enablers and barriers to implementation (7). Treatment of the depressed patient requires insight into depression as a medical condition, psycho-social aspects leading to poor treatment uptake, problems with treatment availability, and treatment disruption, similar to the broader view required for antituberculous treatment (43).…”
Section: Evolution Of Antidepressantsmentioning
confidence: 99%
“…Global deaths associated with major depression were estimated in excess of 2.2 million in 2010 (6), with a 20-fold greater suicide risk than the general population (4). Unlike tuberculosis (1), comprehensive management policies for depression are not universally available (7).…”
Section: Introductionmentioning
confidence: 99%
“…In modern society, stress has become a significant problem that warrants evaluation and management 1 . Dentists frequently encounter patients who suffer psychological and social stress as a result of not being able to masticate effectively 2 .…”
Section: Introductionmentioning
confidence: 99%